International Symposium „Ancient Greek Law – Vectors of Local Idiosyncrasy and Unity“ – Westfälische Wilhelms-Universität Münster, 23.-24. Februar 2023 (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
International Symposium „Ancient Greek Law – Vectors of Local Idiosyncrasy and Unity“ – Westfälische Wilhelms-Universität Münster, 23.-24. Februar 2023